The Gonadal Maturity and Gene Expressions of Female Giant Freshwater Prawn (Macrobrachium rosenbergii) after Dietary Administration of Medroxyprogesterone Acetate - Fajar Anggraeni; Desak Made Malini; Joni Haryadi Damanhuri; Khairul Syahputra; Asep Sopian; Ikhsan Khasani; Imron Imron; Hary Krettiawan (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract